External Apical Root Resorption in Endodontically Treated and Vital Teeth after Orthodontic Treatment: A Retrospective Study - Elchin Karimzada; Elçin Esenlik; Kürşat Er (Turkish Journal of Orthodontics)
Objective: This retrospective study aimed to assess the presence and amount of external apical root resorption (EARR) in endodontically treated teeth (ETT) and contralateral teeth with vital pulp (VPT) following orthodontic treatment. Methods: The study sample included panoramic radiographs of 503 patients (314 females and 189 males; 16.29 years±3.98) with 620 ETT and 580 VPT. The tooth length was measured on digital panoramic radiographs, which were collected at the beginning and end of the orthodontic therapy for each subject. The pre- and post-orthodontic treatment radiographic evaluation included the percentage of EARR in ETT and contralateral VPT for all tooth types. Any relationship between EARR and orthodontic treatment type (one- and two-phase; extraction and non-extraction), duration, and patients’ age and gender were investigated. Mann-Whitney U, Wilcoxon signed rank, Kruskal-Wallis and Spearman correlation tests were applied for comparisons and to test the correlations. Results: A statistically significant difference was observed in all orthodontic treatment groups when ETT and VPT were compared in terms of EARR (p<0.05). EARR was positively correlated with orthodontic treatment duration and type (p<0.05) but was not influenced by patient age or gender. Statistically significant EARR was observed in the two-phase extraction orthodontic treatment group for both ETT and VPT. In VPT, a statistically significant EARR was found in the one-phase extraction treatment group compared with the non-extraction treatment group, whereas no significant difference was found in ETT. Conclusion: ETT showed significantly lower EARR than VPT. ETT can therefore be moved safely during orthodontic treatment.